2008
DOI: 10.1177/13670069080120010701
|View full text |Cite
|
Sign up to set email alerts
|

Loosing grammatical gender in Dutch: The result of bilingual acquisition and/or an act of identity?

Abstract: Academy of Sciences AcknowledgmentI would like to thank two anonymous reviewers for their valuable comments. AbstractIn the Dutch sociolinguistic literature it is often noted that the overgeneralization of common gender, that is, the use of the definite article de where het is required, characterizes the Dutch variety(ies) of immigrants. Recent sociolinguistic research shows that this overgeneralization also occurs in the speech of subsequent generations born in the Netherlands who acquire Dutch as one of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 21 publications
1
21
0
5
Order By: Relevance
“…A quote from Nortier and Dorleijn (2008: 138) The overgeneralization of common gender is characteristic of multiethnolects in the Netherlands. Leonie Cornips (2008) asks the question whether this loss of grammatical gender distinction is the consequence of incomplete second language acquisition only, or an active act of identity. Cornips and de Rooij have published about a variety of Straattaal which is used among young people with a Surinamese background.…”
Section: The Netherlandsmentioning
confidence: 99%
“…A quote from Nortier and Dorleijn (2008: 138) The overgeneralization of common gender is characteristic of multiethnolects in the Netherlands. Leonie Cornips (2008) asks the question whether this loss of grammatical gender distinction is the consequence of incomplete second language acquisition only, or an active act of identity. Cornips and de Rooij have published about a variety of Straattaal which is used among young people with a Surinamese background.…”
Section: The Netherlandsmentioning
confidence: 99%
“…In order to use dummies, learners must have the dummies available in their lexicon, which means that they either incorrectly analyze the meaning of auxiliaries in the target language or are exposed to dummy auxiliaries in the input (Jordens, 1990;Zuckerman, 2001). It has been found that dummies function as markers of identity in Moroccan and Turkish ethnic minority groups living in the Netherlands (Cornips, 2000(Cornips, , 2008El-Aissati et al, 2005). As members of these ethnic communities, the children in our sample may be exposed to dummy auxiliaries.…”
Section: Comparisons With Other Studiesmentioning
confidence: 94%
“…Research on new speakers of Scots Gaelic (Nance 2013), Occitan (Costa 2015), Dutch (Cornips 2008), Yiddish and Breton (Hornsby 2015) has shown them to use some aspects of accent such as intonation pattern to mark local identity affiliation. Nance (2013) disputed the controversial concept of 'incomplete acquisition' by learners, arguing that speakers may actually have fully acquired the language to the extent they need, and that this also affects the speech sounds they use to achieve this communication.…”
Section: Most People Accept That [I Am a Native Speaker] Because I Hamentioning
confidence: 99%